The effects of resistance training applied to elite field hockey players on some strength parameters - Koca, K.: Revan, S. (Turkish Journal of Sport and Exercise, 2023)
This study is intended to investigate the effects of resistance training on the muscular strength and muscular endurance of elite female and male national team field hockey players. 30 female and 30 male national field hockey players aged between 17-28 participated in the study voluntarily. Before the training program of the participants, maximum muscular strength (bench press, leg extension, leg curl, push down) and muscular endurance (30 sec sit-up and 30 sec push-up test) were determined. The training program was applied to the players for 8 weeks, 3 days a week. SPSS 23.0 package program was used for statistical analysis. As a result of the analysis, it was seen that the distributions were normal, and therefore, t-test was used in dependent groups, which is one of the parametric tests, to compare the pre-test and post-test. The significance level was accepted as 0.05. After the 8-week training program, body weight, while body mass index and body fat percentage values decreased in both female and male field hockey players (p<0.05), 1RM values in bench press, leg extension, leg curl and push down applications and 30 sec sit-up and 30 sec push-up values increased significantly compared to the pre-training program (p<0.05). As a result, it can be said that regular resistance training has a positive effect on the body composition, muscular strength and muscular endurance of male and female elite field hockey players.